Root biomass analysis in different forest types: research advances in the Chilean radiata pine forest - Guerra C., Javier; Gayoso A., Jorge; Schlatter V., Juan; Nespolo R., Roberto (Bosque (Valdivia), 2005)
We evaluated the root biomass in Pinus radiata in two different sites and measured the root:shoot index (proportion of roots over aerial biomass). In addition, we undertook a bibliographic review to understand the effects of species and environment on root development. We harvested 27 individuals of Pinus radiata ranging from 3 to 23 years old. Thirteen individuals were selected from a low-quality site and 14 from a high-quality site (according to the soil properties). Root exploration was performed with the semi-mechanical method of extraction, which allows the measurement of every root over 2 mm diameter. The root:shoot ratio was significantly different between the sites, reaching a difference of 5%, which shows that low quality soils allow for higher root:shoot ratios. In addition, we compiled data from 13 tree genera and about 40 species. However, the great variability of the existing data does not allow the inference of any clear effect on root biomass production of forest type, development state, age, and soil.